The paleo-ecological application of mollusks in the calculation of saltwater encroachment and resultant changes in depositional patterns driven by the Anthropocene Marine Transgression - Meeder, John F.; Adelgren, Nathan; Stoffella, Susana L.; Ross, Michael S.; Kadko, David C. (Frontiers in Ecology and Evolution, 2022)
Numerous studies address changes in wetland deposition in response to saltwater encroachment driven by the accelerating rate of sea-level rise, by quantifying temporal changes recovered from a vertical sediment sequence. This is the first landscape scale study, based upon 10 core transects representing the heterogeneity of the Southeast Saline Everglades, Florida. By utilizing the known salinity preferences of molluscan assemblages, a Salinity Index was calculated for each core sequence and the recorded salinity changes identified and dated. Radiometric dating utilizing the 210Pb method provides the rate of sediment accumulation and the date of changes identified in the core. The core transects provide the basis for calculation of the rate of saltwater encroachment by comparing the date of saltwater encroachment and the distance between two cores. Thereby, temporal and spatial changes in other sediment parameters in a landscape can also be quantified, such as organic carbon. This paleo-ecological approach to rapidly changing coastal conditions can be utilized to provide scientists and land managers with a record of the past, rate of changing conditions and provide the basis for predicting the future trajectory of their site. Application of this paleo-ecological approach documented increasing rates of saltwater encroachment associated with accelerating rate of sea-level rise: an average rate of 49.1 between 1895 and 1940, 69.2 between 1940 and 1968, 73 between 1968 and 1995 and 131.1 m/yr between 1995 and 2015. Approximately 1.79 km of saltwater encroachment has occurred since 1995, with three partial reversals because of increased freshwater delivery. Associated with saltwater encroachment are changes in sediment organic carbon, decreasing area of marl production and increasing distribution of mangrove. Although the distance of saltwater encroachment is greater in Florida Bay, both changes in sediment organic carbon and mangrove distribution are much less than in Biscayne Bay coastal basins. This heterogeneity is likely the result of differences in tidal ingress efficiency. At the present rate of saltwater encroachment, the freshwater wetlands are predictably lost within a century.